2018
DOI: 10.1080/01634372.2018.1499575
|View full text |Cite
|
Sign up to set email alerts
|

Key Determinants to using Telehealth Technology to Serve Medically Ill and Depressed Homebound Older Adults

Abstract: Despite the increasing evidence for the effectiveness of telehealth technology in screening and treating chronic diseases, and comorbid depression among older adults, they have been slowly adopted by home health care (HHC) agencies. Therefore, this study aimed to identify factors that determine telehealth technology adoption. Twenty directors from the National Association for Homecare & Hospice member agencies completed a 45-min telephone interview. Questions were asked regarding their perceptions of telehealt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…Some limitations providers identified, such as access to technology, are well documented (Kim et al, 2019; Kozikowski et al, 2019). Practices, health systems, and payers can play an important role in addressing these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations providers identified, such as access to technology, are well documented (Kim et al, 2019; Kozikowski et al, 2019). Practices, health systems, and payers can play an important role in addressing these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of organisational effectiveness is a significant telemedicine adoption barrier, indicating that current telemedicine projects fail to meet their organisational goals regarding effectivity measures. Effective tele-monitoring systems have been shown to reduce hospitalisations and mortality risk among patients with chronic heart failure (Kim, Gellis, Bradway, & Kenaley, 2018). Many e-Health project plans fail due to inadequate organisational policy integration into practice (Gagnon et al, 2009).…”
Section: Organisational Barriersmentioning
confidence: 99%
“…A study on telehealth adoption among US hospitals showed that the rate of hospital telehealth is associated with differences in state policy [1]. The most common aspect of research is on an organisational level, i.e., telehealth adoption in hospitals [46] or among individuals from specific groups, such as older people [47][48][49]. As telehealth is considered at an individual level (clinician to clinician, clinician to patient), it is also connected with the health professional workforce andto some extendwith electronic health records [50].…”
Section: E-health Capacity Buildingmentioning
confidence: 99%